Mathematical Simulation of Heat Impact of Heated Up to High Temperatures Particle on Human Skin: Simple One-Dimensional Statement - Solodkin, Andrey S.; Ponomarev, Konstantin O. (MATEC web of conferences, 2014)
It is developed physical and mathematical models of process of a heat transfer between skin and a heating source - single heated up to high temperatures particle. Temperature distribution in system “particle-skin” for heated wooden particle is obtained. The data obtained during work can be used for addition of already available materials on the given subjects and comparisons of influences on a skin of various factors, and also can be useful to development of new systems of protection against the influences damaging factors in the conditions of fire.